2022
DOI: 10.3390/ijms232416039
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Recognition Properties from an Intermediate Structural State of the UreA Transporter

Abstract: Through a combination of comparative modeling, site-directed and classical random mutagenesis approaches, we previously identified critical residues for binding, recognition, and translocation of urea, and its inhibition by 2-thiourea and acetamide in the Aspergillus nidulans urea transporter, UreA. To deepen the structural characterization of UreA, we employed the artificial intelligence (AI) based AlphaFold2 (AF2) program. In this analysis, the resulting AF2 models lacked inward- and outward-facing cavities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…We have not yet functionally characterized the putative DUR3-like urea transporters of T. fluviatilis, but the presence of most of the amino acid residues that were reported to be essential for the function of UreA, the respective DUR3 protein in A. nidulans [18], and that are present in DUR3-like of T. squamosa [20] (see Figure 1) strongly indicates functionality. In a recent publication, however, Sanguinetti et al [38] convincingly demonstrated that the amino acid residues W82, W84, N279, and T282 in UreA of A. nidulans are directly involved in urea binding and translocation. All four amino acid residues occur in Tf UT-B, but only W84 is present in Tf UT-A1-A3 and DUR3-like of T. squamosa (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not yet functionally characterized the putative DUR3-like urea transporters of T. fluviatilis, but the presence of most of the amino acid residues that were reported to be essential for the function of UreA, the respective DUR3 protein in A. nidulans [18], and that are present in DUR3-like of T. squamosa [20] (see Figure 1) strongly indicates functionality. In a recent publication, however, Sanguinetti et al [38] convincingly demonstrated that the amino acid residues W82, W84, N279, and T282 in UreA of A. nidulans are directly involved in urea binding and translocation. All four amino acid residues occur in Tf UT-B, but only W84 is present in Tf UT-A1-A3 and DUR3-like of T. squamosa (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, the residues W82, N279, T282, Y437, and S446 of UreA are missing in Tf UT-A1-A3 and the DUR3-like urea transporter of T. squamosa, but are present in Tf UT-B. For W82, N279, and T282, direct involvement in urea binding and translocation has recently been shown [38], whereas Y437 seems to be involved in substrate selectivity and S446 is necessary for the correct sorting of UreA to the membrane [39].…”
Section: Structural Features Of Putative Dur3-like Urea Transporters ...mentioning
confidence: 99%